Handbook of contemporary Japanese religions - Prohl, Inken.; Nelson, John K. 1953- (Brill Handbooks on Contemporary Religion, 2012)
Representing work by some of the leading scholars in the field, the chapters of this handbook survey the transformation and innovation of religious traditions and practices in contemporary Japan. Readers will find lively scholarly studies about changes in the traditional institutions of Buddhism and Shinto, vivid examples of social activism as well as the so-called "new religions," examination of the relationship between religion and the state, and analysis of the religiosity of individuals encompassed by "spirituality," pilgrimage and tourism, and the marketing of religions. This groundbreaking collection of scholarly papers helps to map out the fascinating complexity and dynamism of religion in contemporary Japanese society and culture.